Structural-Cultural Continuum of Strategic Organizational Changes - P. A. Mikhnenko (Управленческие науки, 2016)
The purpose of the research is the substantiation of urgency in complex analysis of interdependence and reciprocal conditionality of company’s structural and cultural characteristics in managing strategic organizational changes. The concept of structural-cultural continuum as a set of complementary variables creating the unique character of the organizational system is based on the thesis of synergy of the organizational culture coordination profile. The article offers the approach to examining insufficiently studied problems, i.e. identifying the nature of the influence of the structural-cultural continuum on the company’s performance. The analysis results of the synthetic interdependence of the organization’s configuration as well as its structural and cultural features allow to draw conclusions about the organization’s ability to implement strategic organizational changes with optimal intensity. The main results of the research are: substantiation of the concept of the organization’s structural- cultural continuum (SCC); the procedure of formation and the results of the analysis of the SCC multiplier matrix; the graph presenting the dependence of intensity maximum values of organizational changes on the degree of the personnel’s integration and expertise; expert judgments on the degree of impact of the SCC conjunction on developing employees’ special skills in organizational change; the SCC conjunction field on the zonal map of the organization strategic adaptation as well as the analysis results of their positioning. The results and the conclusions can be used both to substantiate the ways of optimization of the organization’s structural-cultural continuum for its strategic development and to predict the adaptive capacity of the organizational configurations under various environmental conditions.